Processo automatizado de triagem de envelopes de cartas e correspondências - Bertoleti, Levy (2018)
This is about a proof concept involving planning and execution of a prototype for developing a compact envelopes sorting machine to be used in CDD's (Warehouses for delivering centers) of the Post Office, who does a sorting of letters by reading the CEP (zip code). This machine aims to replace manual labor, on average, with a group of approximately 30 postmen, sorting around 30 thousand objects in 40 different positions, by each CDD. This mechanization alternative should bring some benefits to the company such as cost reduction for the post office, optimization of time, a significant improvement in the employee satisfaction index, improvement of quality control and modernization of the company. During the semester, an idealization of a prototype was prepared using the Pahl & Beitz´s methodology and QFD methodology, both presented on TCC 1; this prototype was created as a proof of concept instead of a commercial product. It has all necessary parts of a sorting machine (movement of letters, reading and analysis of data, and posterior separation to deliver). A market survey was done of what has already been available and what similar services are already offered in the market, besides evaluating material cost and economic and commercial feasibility studies of the product. Studies about components and zip code reading softwares will also be completed. Later, studies about a functional prototype of a letter and envelopes sorting machine will be developed. After the approval of the prototype, resources will be raised and sponsored for the production of the machinery and its future commercialization. The main attempt will be marketing the product to the company Post Office as well as training of people, maintenance of the equipment and sale or rental of the machine. The equipment should initially only operate small envelopes (standard RPC - recommended by the post office), and can be improved later to include envelopes and correspondence with other dimensions, according to the customer's needs. The machine must have a relatively low / affordable cost in terms of market competition, in order to economically make it possible to market it. Such a study can be finished by comparing the cost of the number of employees working on the sorting of the cards by a time X, with the cost of the work developed by the proposed equipment.